Effect of different loads of treadmill exercise on Th1/Th2 cytokine balance in rat splenocytes - Gholamnezhad, Zahra; Boskabady, Mohammad Hossein; Hosseini, Mahmoud (Journal of Applied Biomedicine, 2018)
The effect of moderate and overtraining exercise on Th1/Th2 balance was evaluated in rat splenocytes. Male Wistar rats were divided into sedentary control (C), moderately trained (MT; V = 20 m/min, 30 min/day, 8 weeks), overtrained (OT; V = 25 m/min, 60 min/day, 11 weeks) and recovered after overtraining (OR) (OT plus 2 weeks recovery) groups. At the end of study, cell viability, proliferation, interleukin 4 (IL-4) and interferon-γ (IFN-γ) secretion were evaluated in non-stimulated, phytohemagglutinin (PHA) and concavaline A (Con A)-stimulated splenocytes. Cell viability increased in MT and OR groups compared to control. Cell proliferation was higher in OR group than other groups. IL-4 concentration in PHA-stimulated cells from MT and OT groups, and IL-4 concentration in Con A-stimulated cells from OR and OT groups, were higher than the control group, but not for IFN-γ. In non-stimulated cells, IFN-γ/ IL-4 ratio was higher than MT and OT groups. In PHA and Con A-stimulated cells, IFN-γ/ IL-4 ratio was lower in exercise groups than control. We previously showed that moderate exercise increases Th1 cytokines in serum, but in splenocytes, Th2 or Th1 response may increase depending on the type of mitogen stimulation. Two-week recovery restored Th1/Th2 balance, only in non-stimulated splenocytes of overtrained animals.
Keywords: Physical Exertion; adaptivní imunita; Animals; proliferace buněk; Cytokines; cytotoxické T-lymfocyty; Rats, Wistar; slezina; cytokiny; Adaptive Immunity; kultivované buňky; Models, Animal; Cells, Cultured; T-Lymphocytes, Cytotoxic; Male; Spleen; Cell Proliferation; tělesná námaha; zvířata; mužské pohlaví; modely u zvířat; potkani Wistar